Формування фінансової стійкості як запорука уникнення банкрутства - Коваленко, Анна Сергіївна (Хмельницький національний університет, 2015)
У статті надано визначення банкрутства сільськогосподарських підприємств як кінцевої стадії фінансової нестабільності. Проведено уточнення змісту фінансової стійкості підприємства. Визначена роль фінансової стійкості у діяльності суб'єктів господарювання. Виявлені особливості та розглянуті основні етапи формування фінансової стійкості підприємств сільського господарства. Основним завданням фінансової стабілізації визначено послідовне подолання проявів кризових явищ.

The analysis of the bankruptcy interpretations and the insolvency of author's definition of farm bankruptcy as the final stage of financial instability are provided in the article. A clarification of the content of financial stability of the company is conducted. It is proved that the foundation of financial stability is the ability to effectively extended reproduction. The role of financial stability in the business entities is defined. The basic objectives of financial stability are detected. The basic features and stages of financial sustainability of agricultural enterprises are underlined. The main objective of financial stability is defined as overcoming of the manifestations of the crisis. The need to find appropriate methodological support to the particularities of the flow of financial processes in agriculture is underlined.
Formation of financial stability as a key to avoid bankruptcy
Keywords: банкрутство; фінансовий стан; фінансова стійкість; стабілізація; криза; сільськогосподарське підприємство; bankruptcy; financial condition; financial stability; stabilization; crisis; agricultural enterprise